Emergency Traffic Signal Control System for Ambulance - Patil, Vishal S; Sawale, Priyanka; Kale, Pooja (International Journal of Computer Sciences and Engineering, 2025)
We all knows with increase in Traffic Congestion and growing population increases the demand for emergency vehicles services arises, time can be friend or a worst enemy in emergency lesser the time to travel greater will be efficiency each second turn by the red light and traffic blocking is the critical thing which routes the emergency site. So how to prioritized emergency vehicles is the question for our mind. How much the seconds matter is one doctors who can save life, no even we engineers can save the life. In this human care about time but not a life. Even when ambulance is stuck in traffic people don’t give the way for ambulance to move safely. So traffic congestion has become major problem around us. As the result of the rapid growth of technology and engineering field the life of mankind has got automated.